Eksplorasi Ocean Literacy Calon Guru IPS di Makassar: Urgensi Pendidikan Berkelanjutan Berbasis Pesisir - Asmaul Husnah Amiruddin; Alwi Usra Usman (Majalah Ilmiah METHODA, 2026)
This study aims to explore the level of ocean literacy among prospective social studies teachers in Makassar and analyze the urgency of coastal-based sustainable education in supporting marine literacy. This study employed a quantitative approach with a descriptive-comparative design. Data were collected through a structured questionnaire measuring six dimensions of ocean literacy synthesized from the Ocean Literacy Framework developed by NOAA and UNESCO and UNESCO’s environmental education framework, namelyawareness, knowledge, attitude, education, communication, and behavior. The study involved 185 respondents consisting of Social Studies Education students and teacher professional education (PPG) participants at Universitas Negeri Makassar. Data were analyzed using descriptive statistics,Independent Samples T-Test,and Spearman correlation. The findings reveal that the level of ocean literacy among prospective social studies teachers remains predominantly low to moderate across most dimensions. The behavior dimension emerged as the weakest aspect, indicating a knowledge-behavior gap between ecological knowledge and actual environmental behavior. Comparative analysis also showed no significant difference in ocean literacy between Social Studies students and PPG participants. These findings highlight the importance of strengthening coastal-based sustainable education to foster ecological awareness, values, and behaviors that support marine sustainability.